Is European Money Demand Still Stable? - Kai Carstensen (Kiel Institute for World Economics (IfW), 2004)
This paper analyzes the question whether money demand in the Euro area has undergone a structural change in recent time when M3 money growth has considerably overshot the reference value set by the European Central Bank (ECB). It is found that conventional specifications of money demand have in fact become unstable while specifications which are augmented with equity returns and volatility remain stable. Using such an augmented specification, it turns out that the excessive M3 growth rates can largely be attributed to the stock market downswing and do not put a measurable threat to price stability.
Keywords: E41; 330; Money demand; EMU; excess liquidity; Geldnachfrage; Börsenkurs; Volatilität; Schätzung; EU-Staaten